Macam Macam Etika Kepolisian - Chaerudin Loma Faisal; Rahmad Ramadhan (JOURNAL SAINS STUDENT RESEARCH, 2025)
Police ethics are moral norms that serve as a reference for police officers in carrying out their duties. The purpose of this study is to identify and examine various forms of police ethics that are applied in carrying out duties and obligations. This study shows that police ethics include professional ethics, social ethics, and institutional ethics. Professional ethics include integrity, professionalism, and responsibility. Social ethics include empathy, tolerance, and awareness of the community. Institutional ethics include loyalty, order, and collaboration. The results of this study indicate that the application of good ethics in the police can strengthen public trust and improve the quality of police services.